DEVELOPING JIGSAW MODEL FOR YOUNG LEARNERS; PROMOTING MEANINGFUL AND AGE APPROPRIATE SPEAKING ACTIVITIES - Su, Yosefina Rosdiana (STKIP Santu Paulus Ruteng, 2016)
Abstract: Developing Jigsaw Model for Young Learner; Promoting Meaningful and Age Appropriate Speaking Activities. The project with young learner is not an easy one. When teaching young learners, we constantly have to keep in mind the fact that what we have in front of us is a mixed class with varied abilities, expectations, different level of motivation, knowledge and learning styles. Thus, we need to vary our approaches and offer as much opportunity as possible to make the whole class find something to help them to expand and grow. This article provides some developing speaking activities based on the principles of jigsaw which appropriate with young learners stage of development. The provided stages of activities are designed as simple as possible so that it can be applied by both experience and inexperience English teachers of elementary school to promote the fun and meaningful learning experiences for their young learners. Keywords: Develop, Jigsaw, Young Learners, Speaking Abstrak: Pengembangan Model Jigsaw Bagi Peserta Didik Usia Dini; Menciptakan Kegiatan Berbicara Yang Bermakna dan Tepat Usia. Tugas yang berkaitan dengan peserta didik usia dini bukanlah hal yang mudah. Ketika kita berhadapan dengan peserta didik usia dini, yang ada dihadapan kita adalah kelompok belajar gabungan yang memiliki kemampuan yang bervariasi, harapan, tingkat motivasi, pengetahuan, dan gaya belajar yang berbeda-beda. Dengan demikian, kita perlu menerapkan pendekatan yang bervariasi and menawarkan kesempatan sebanyak mungkin agar seluruh kelas menemukan sesuatu yang bisa membantu mereka untuk bertumbuh dan berkembang. Artikel ini menyediakan beberapa kegiatan belajar berbicara yang dikembangkan dengan menggunakan strategi jigsaw pada konteks peserta didik usia dini. Langkah-langkah pembelajaran yang disajikan dirancang sesederhana mungkin sehingga dapat diaplikasikan oleh baik guru-guru sekolah dasar yang sudah berpengalaman maupun yang belum berpengalaman dalam rangka menciptakan pengalaman belajar yang menyenangkan dan bermakna bagi peserta didik usia dini. Kata Kunci: Pengembangan, Model Jigsaw, Berbicara, Peserta Didik Usia Dini